Axial bonds at the T1 Cu site of Thermus thermophilus SG0.5JP17‐16 laccase influence enzymatic properties. Issue 5 (9th April 2019) - Zhu, Yanyun; Zhang, Yi; Zhan, Jiangbo; Lin, Ying; Yang, Xiaorong
Abstract : Laccase is a multi‐copper oxidase which oxidizes substrate at the type 1 copper site, simultaneously coupling the reduction of dioxygen to water at the trinuclear copper center. In this study, we used site‐directed mutagenesis to study the effect of axial bonds between the metal and amino acid residue side chains in lacTT. Our kinetic and spectral data showed that the replacement of the axial residue with non‐coordinating residues resulted in higher efficiency ( k cat / K m ) and a lower Cu 2+ population at the type 1 copper site, while substitution with strongly coordinating residues resulted in lower efficiency and a higher Cu 2+ population, as compared with the wild‐type. The redox potentials of mutants with hydrophobic axial residues (Ala and Phe) were higher than that of the wild‐type. In conclusion, these insights into the catalytic mechanism of laccase may be of use in protein engineering to fine‐tune its enzymatic properties for industrial application. Abstract : In this study, we replaced the axial ligand Met460 of the type 1 Cu in Thermus thermophilus SG0.5JP17‐16 laccase by site‐directed mutagenesis. We then performed spectral and kinetic assays and compared structures and redox potentials to evaluate how the axial ligand–metal bond at the type 1 Cu site influences the catalytic behavior of laccase.